DUKUNGAN SOSIAL ORANG TUA, HARDINESS DAN STRES AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Elik, Helmy Krisnayanti; Ama, Roy Gustaf Tupen; Evianawati, Evianawati; S. Bete, Rufina Nenitriana (Dharmas Education Journal (DE_Journal), 2024)
This research aims to determine the relationship between parental social support and hardiness and academic stress in final year students. The research method used is quantitative correlational. The research sample is active final year students, female and male, who are working on their thesis/final project. The number of samples in this research was 200 students. The research sampling technique used accidental sampling. The research instrument was used to measure the 3 variables, namely the academic stress scale, hardiness scale and parental social support scale. The research data analysis method uses product moment analysis and regression. Research findings show that, (1) there is a negative relationship between hardiness and academic stress with rxy= -0.714, (p<0.000); (2) there is a negative relationship between parental social support and academic stress with a value of rxy= - 0.712 (p<0.000); (3) there is a stimulant relationship between parental social support and hardiness with academic stress with a value of r = 0.761, F= 135.72 (p<0.000). The effective contribution of family social support and hardiness to academic stress was 57.9%. The implication of this research is that final year students have a tough personality (hardiness) and there needs to be social support from parents for students while working on their thesis so that students avoid high academic stress.